Sleep disorder risk factors among student athletes - Monma, Takafumi; Ando, Akira; Asanuma, Tohru; Yoshitake, Yutaka; Yoshida, Goichiro; Miyazawa, Taiki; Ebine, Naoyuki; Takeda, Satoko; Omi, Naomi; Satoh, Makoto; Tokuyama, Kumpei; Takeda, Fumi (Sleep medicine, 2018)
To clarify sleep disorder risk factors among student athletes, this study examined the relationship between lifestyle habits, competition activities, psychological distress, and sleep disorders. Student athletes (N = 906; male: 70.1%; average age: 19.1 ± 0.8 years) in five university sports departments from four Japanese regions were targeted for analysis. Survey items were attributes (age, gender, and body mass index), sleep disorders (recorded through the Pittsburgh Sleep Quality Index), lifestyle habits (bedtime, wake-up time, smoking, drinking alcohol, meals, part-time jobs, and use of electronics after lights out), competition activities (activity contents and competition stressors), and psychological distress (recorded through the K6 scale). The relation between lifestyle habits, competition activities, psychological distress, and sleep disorders was explored using logistic regression analysis. Results of multivariate logistic regression analysis with attributes as adjustment variables showed that “bedtime,” “wake-up time,” “psychological distress,” “part-time jobs,” “smartphone/cellphone use after lights out,” “morning practices,” and “motivation loss stressors,” were risk factors that were independently related to sleep disorders. Sleep disorders among student athletes are related to lifestyle habits such as late bedtime, early wake-up time, late night part-time jobs, and use of smartphones/cellphones after lights out; psychological distress; and competition activities such as morning practices and motivation loss stressors related to competition. Therefore, this study suggests the importance of improving these lifestyle habits, mental health, and competition activities. •Securing sleep duration is most important to prevent sleep disorders (SDs).•Psychological distress is the next highest risk factor for SDs.•Improving both lifestyles and the competitive environment is effective against SDs.